Ocular involvement in diabetic patients attending tertiary care centres of eastern U.P., India: a prospective study - Saxena, Nutan; Jain, A. M.; Khan, Perwez; Agarwal, Ruchika; Tiwari, Harish Chandra; Thakur, Anita (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus is increasing day by day in developing countries especially in India. It is a main treatable cause of morbidity in eye. Diabetic cataract, neovascular glaucoma and retinopathy are important ocular complications due to diabetes mellitus. The objective was to study the variations in ocular complications in patients of diabetes mellitus. Methods: A prospective study from July 2012 to June 2013 was conducted in RMCH and RC, Kanpur & GSVM Medical College, Kanpur. One hundred one selected diabetic patients who are having abnormal slit lamp and fundus examination were included in this study. Results: In our study it was found that more the duration of diabetes, greater the severity of diabetes. Well controlled diabetics have lesser complications in eyes due to diabetes. Conclusion: Patient’s age, sex, duration and control of diabetes play important role in development and severity of complications in eye due to diabetes mellitus.